Improving menopausal women’s knowledge through community-based health education and screening: A community engagement program in Takalar, Indonesia - Sri Wahyuni; Asridawati Akib; Rika Riyandani; Dewi Umbarsari; Rosmiaty Pammu; Ria Wahyuni; Falia Alwan; Hildawati Rumagutawan (Edukasi Ilmiah Indonesia, 2026)
Menopause is a natural stage of women’s lives that is often accompanied by physical, psychological, and metabolic changes, including increased risks of hypertension, diabetes mellitus, obesity, osteoporosis, and cardiovascular disease. This community engagement program aimed to improve menopausal women’s knowledge and awareness through integrated health education and basic screening in Kampung Beru Village, Galesong District, Takalar Regency, Indonesia. The activity involved 24 menopausal women and was conducted using lectures, discussions, pretest–posttest assessment, blood pressure measurement, blood glucose testing, anthropometric assessment, body mass index calculation, and individual counseling based on screening results. The findings showed that all participants experienced an increase in knowledge after the educational intervention, with 24 positive ranks and no negative ranks or ties. The Wilcoxon signed-rank test demonstrated a statistically significant improvement between pretest and posttest scores (Z = −3.314; p = 0.001). Participants also showed high enthusiasm and active involvement throughout the program. The activity increased understanding of menopausal health, encouraged routine health screening, and supported early identification of degenerative disease risk factors. In conclusion, community-based health education combined with simple screening is an effective approach to strengthening health literacy, promoting preventive behavior, and supporting healthier ageing among menopausal women in rural communities and primary care.